Evaluation of the Effect of Educational Intervention on the Error of Insurance Documents on Deductions in Hospitalization Records - Mahmood Mousavi; Zohreh Karimiankakolaki (Journal of Social Behavior and Community Health)
Background: The aim of this study is to consider the effect of an educational intervention on the error rate of insurance documents in the deductingof hospitalization records of Covid-19 patients' health insurance among hospital staff. Methods: The target population of this semi-experimental study was all personnel involved in the management of patients with Covid-19. Among the hospitals of the Covid-19 site in Chaharmahal and Bakhtiari provinces, one hospital was selected as the educational target group (24 individuals) and one hospital was considered as the control group (16 individuals) by lottery. To measure the effectiveness of education, the sample size of all cases of 19 patients with health insurance in two hospitalsduring two periods of October and March 2016 was determined. Data collection was performed by checklists and direct reviews of files, health insurance system and hospital HIS system. Data analysis was fulfilled using SPSS21 software. Results: The number of deductions in the case of "Covid 19 hospitalized patients" of the health insurance decreased significantly in the intervention hospital  from 1833 to 933 (p < .005) and increased in the control hospital from 447 to 2712 (p < .005). In the intervention hospital, the highest decrease in deductions in the hoteling service was from 235 (12.8%) to 2 (0.2%) cases (p < .001) and for medicines from 335 (18.2%) to 56 (6%) cases (p < .001). Conclusion: The results demonstrated thatstaff training on the error in Covid-19 insurance documents during the corona pandemic outbreak has reduced the number of insurance deductions in Covid-19 patients' records.